Intensi dan Perilaku Berwirausaha di Kota Tangerang Selatan [The Entrepreneurial Intention and Behavior in Tangerang Selatan] - Alfian, Florencia Putri; Layman, Chrisanty V. (Milestone: Journal of Strategic Management, 2022)
This study aims to examine the effect of Entrepreneurship Education, Inspiration, Resources, Subjective Norms, Attitudes, Behavioral Control Perceptions, Entrepreneurial Intentions and Entrepreneurial Behavior. The sampling technique in this study was non-probability sampling, namely purposive sampling where the respondents were students who received Entrepreneurship Education lessons. The number of samples as many as 280 respondents with data collection methods using online questionnaires. The analytical method used is statistical with Partial Least Square - Structural Equation Modeling (PLS-SEM) with SmartPLS 3 application. The results show that Entrepreneurship Education has a positive and significant effect on attitudes and behavioral control, but has no significant effect on subjective norms. Inspiration has a positive and significant effect on attitudes, subjective norms, behavioral control. Resources have a positive effect on subjective norms, attitudes have a positive effect on entrepreneurial intentions. Subjective norms have a positive and significant effect on perceptions of behavioral control, entrepreneurial intentions, but not significant on entrepreneurial intentions. The perception of behavioral control has a positive effect on entrepreneurial intentions and entrepreneurial behavior, but has no significant effect on entrepreneurial behavior.BAHASA INDONESIA ABSTRACTPenelitian ini bertujuan untuk menguji pengaruh Pendidikan Kewirausahaan, Inspirasi, Sumber Daya, Norma Subjektif, Sikap, Persepsi Kontrol Perilaku, Intensi Berwirausaha dan Perilaku Berwirausaha. Teknik pengambilan sampel pada penelitian ini adalah non-probability sampling yaitu purposive sampling di mana responden merupakan Mahasiswa yang mendapatkan pelajaran Pendidikan Kewirausahaan. Jumlah sampel sebanyak 280 responden dengan metode pengumpulan data menggunakan kuesioner secara daring. Metode analisis yang digunakan adalah statistic dengan Partial Least Square – Structural Equation Modeling (PLS-SEM) dengan aplikasi SmartPLS 3. Hasil penelitian menunjukan bahwa Pendidikan Kewirausahaan berpengaruh positif dan signifikan terhadap sikap dan kontrol perilaku, tetapi tidak berpengaruh signifikan terhadap norma subjektif. Inspirasi berpengaruh positif dan signifikan terhadap sikap, norma subjektif, kontrol perilaku. Sumber daya berpengaruh positif terhadap norma subjektif, sikap berpengaruh positif terhadap intensi berwirausaha. Norma subjektif berpengaruh positif dan signifikan terhadap persepsi kontrol perilaku, intensi berwirausaha, namun tidak signifikan terhadap intensi berwirausaha. Persepsi kontrol perilaku berpengaruh positif terhadap intensi berwirausaha dan perilaku berwirausaha, namun tidak berpengaruh signifikan terhadap perilaku berwirausaha.